GIS modelling for the potential high risk areas of dengue outbreaks according to the environmental factors - Oo, Eam Seang,1987-, author; Mohamad Nor Said, supervisor; Fakulti Geoinformasi dan Harta Tanah (2011)
Project Paper (Sarjana Muda Sains (Geoinformatik)) - Universiti Teknologi Malaysia, 2011